2014
DOI: 10.4103/0019-5413.136228
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between neurological recovery and magnetic resonance imaging in Pott’s paraplegia

Abstract: Background:Spinal cord/nerve root compression secondary to a tubercular epidural abscess leads to neurological deficit. Depending on the extent and duration of compression, the end result after treatment may vary from complete recovery to permanent deficit. ASIA has been used extensively to correlate between MRI and neurological status due to traumatic spine injuries. MRI has stood as an invaluable diagnostic tool out of the entire range of current imaging modalities. However, inspite of considerable literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Some of the studies have reported thoracolumbar level as most commonly involved, 7 whereas others have found thoracic vertebrae as the most commonly affected. 22,23 In our study, more than one-third of cases (n = 112 or 35.89%) presented with intact neurology, whereas 97 (31.0%) were AIS D, 65 (20.83%) AIS C, 8 (2.50%) AIS B and 30 (9.61%) AIS A. There are only few studies documenting the neurological grading in spinal tuberculosis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Some of the studies have reported thoracolumbar level as most commonly involved, 7 whereas others have found thoracic vertebrae as the most commonly affected. 22,23 In our study, more than one-third of cases (n = 112 or 35.89%) presented with intact neurology, whereas 97 (31.0%) were AIS D, 65 (20.83%) AIS C, 8 (2.50%) AIS B and 30 (9.61%) AIS A. There are only few studies documenting the neurological grading in spinal tuberculosis.…”
Section: Discussionmentioning
confidence: 66%
“…9 Most patients of spinal tuberculosis present with mild to no neurological deficit. 10,11 Combination of conservative treatment in the form of anti-tubercular drugs and operative intervention such as simple decompression and stabilization has been reported to result in good clinical outcome in patients presenting with mild-to-moderate deficit. [12][13][14] Although there are limited studies regarding factors affecting neurological recovery in tuberculosis of spine, delay in starting treatment, cord compression, spinal extension of abscess and involvement of more than two vertebras were considered bad prognostic factors in medically treated patients of spinal tuberculosis according to one study.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand in postoperative 4.8% were grade B, 33.3% were grade D and 61.9% were grade E. The difference was statistically significant (P<0.001) where CI is 95%. Study shows before starting treatment 1 patient (2.08%) was in ASIA A, 2 (4.16%) were in ASIA B, 9 (18.75%) were in ASIA C, 36 (75%) were in ASIA D and 12 (20%) were in ASIA E 19 . After 6 months of therapy 30 (90%) patients in ASIA D and 5 (55.5%) in ASIA C had complete neurological recovery.…”
Section: Discussionmentioning
confidence: 92%
“…A.K. Gupta et al [21] отметили, что размер эпидурального абс-цесса может рассматриваться как прогностиче-ский фактор для восстановления неврологического дефицита.…”
Section: клиническая фармакологияunclassified